Evaluation of a novel C‐Arm draping technique to minimize surgical field contamination and surgery time. Issue 7 (21st June 2021) - Darbandi, Aria; Pujari, Amit; Lin, Carol
Abstract: Background: The purpose of this study is to compare the sterility of three C‐Arm draping techniques: the clip‐drape, sterile pouch, and a novel drape tower method. We hypothesize that our novel technique will minimize floor contamination from reaching the surgical field while allowing the C‐Arm machine to rotate between lateral and anterior–posterior positions more quickly. Methods: Five trials consisting of rotating the C‐Arm and simulating surgeon movement were run using each technique. Ultraviolet light illuminating melamine powder was used to represent floor contamination. Measurements of melamine powder encroachment on the drapes were taken using the top of the C‐Arm in lateral position as the reference point. The time needed to assemble, deploy, and retract the C‐Arm was measured for each technique. The gown, gloves, and mayo stand were also examined after each trial for contamination. Results: Compared to the clip drape, the drape tower prevented contamination from reaching the C‐Arm by an additional 30.5 cm (95% confidence interval (CI): 17.0–43.9, P  < 0.001). The drape tower had faster deployment and retraction times than both the clip drape ( P  < 0.001 and P  < 0.001, respectively) and sterile pouch ( P  = 0.011 and P  < 0.001, respectively). The clip drape and sterile pouch exhibited glove contamination in two (40%) simulations, while the drape tower showed no instances of contamination ( P  = 0.255). Conclusions: The novel drape tower technique limits the encroachment of floor contamination onto sterile drapes. It should be considered as an alternative draping method for lower extremity surgery. Abstract : In this current study, the novel "drape tower" technique for the C‐Arm intraoperative fluoroscopy device is assessed. The drape tower requires no adjustment during rotation, limiting the risk of contamination and saving surgical time.